1954
DOI: 10.1515/znb-1954-0802
|View full text |Cite
|
Sign up to set email alerts
|

Esterbindungen im Prokollagen

Abstract: C 12 H 22 CdN4O14, triclinic, P¯ (no. 2), a = 7.188(2) Å, b = 8.895(3) Å, c = 9.771(3) Å, α = 63.148(3)°, β = 76.750(3)°, γ = 66.225(3)°, V = 509.2(3) Å 3 , Z = 1, Rgt(F) = 0.0253, wR ref (F 2 ) = 0.0676, T = 296(2) K. CCDC no.: 1484775The crystal structure is shown in the gure. Tables 1 and 2 contain details of the measurement method and a list of the atoms including atomic coordinates and displacement parameters. Source of materialThe title compound was synthesized by a hydrothermal method under autogenous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1955
1955
1964
1964

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…The more soluble fraction, procollagen, has apparently a very small number of N-terminal groups, and typical collagen has none unless it is degraded prior to analysis. On the other hand, Grassmann and co-workers (107,108,109) found an appreciable number of amino alcohols formed upon reduction; the yield amounted to about 5 per cent of all of the residues, or one thousand times the N-terminal residues of procollagen. Since the same amount was found with and without prior esterification, the authors concluded that these amino alcohols were derived from originally ester linked C-terminal amino acids, presumably involving the carbohydrate moiety of collagen.…”
Section: Structural Analysis Of Proteinsmentioning
confidence: 98%
See 2 more Smart Citations
“…The more soluble fraction, procollagen, has apparently a very small number of N-terminal groups, and typical collagen has none unless it is degraded prior to analysis. On the other hand, Grassmann and co-workers (107,108,109) found an appreciable number of amino alcohols formed upon reduction; the yield amounted to about 5 per cent of all of the residues, or one thousand times the N-terminal residues of procollagen. Since the same amount was found with and without prior esterification, the authors concluded that these amino alcohols were derived from originally ester linked C-terminal amino acids, presumably involving the carbohydrate moiety of collagen.…”
Section: Structural Analysis Of Proteinsmentioning
confidence: 98%
“…However, the latter reagent has been reinvestigated quite intensively by Grassmann and co-workers (107,108,109). Those authors conclude that no untoward reactions such as reduction of amide or peptide bonds occurs, even in several hours in boiling tetrahydrofuran; in contrast the results of Crawhall & Elliott indicate appreciable reduction of the amide bonds (110,111).…”
Section: Structural Analysis Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grossman, Endres, and Steber (1954) have even suggested that the hydroxyl grouping of hydroxyproline may well be involved in even stronger bonding, namely, ester formation with the carboxyl group of an amino-acid residue. Proline, lacking this hydroxyl group, cannot give rise to any such bonding.…”
Section: Figmentioning
confidence: 99%
“…On the other hand, satisfactory results can be obtained on small peptides which are sufficiently soluble to allow reduction to take place at a reasonable rate of low temperature. Recently, Grassmann, Endres & Steber (1954) have suggested that procollagen contains ester bonds because it yields amino alcohols on treatment with lithium borohydride at the boiling point of THF. In a subsequent paper Bioch.…”
Section: H Nhmentioning
confidence: 99%